2004
DOI: 10.2105/ajph.94.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Poor Smokers, Poor Quitters, and Cigarette Tax Regressivity

Abstract: The traditional view that excise taxes are regressive has been challenged. I document the history of the term regressive tax, show that traditional definitions have always found cigarette taxes to be regressive, and illustrate the implications of the greater price responsiveness observed among the poor. I explain the different definitions of tax burden: accounting, welfare-based willingness to pay, and welfare-based time inconsistent. Progressivity (equity across income groups) is sensitive to the way in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 13 publications
1
90
0
4
Order By: Relevance
“…However, Smed et al 24 found that food taxes were only slightly regressive and that lower-income households reduced their consumption proportionately more than wealthier households, as has been observed with tobacco taxes. 49 Combining food taxes with subsidies could help alleviate potential regressivity by enabling consumers to switch to more healthy products without incurring additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Smed et al 24 found that food taxes were only slightly regressive and that lower-income households reduced their consumption proportionately more than wealthier households, as has been observed with tobacco taxes. 49 Combining food taxes with subsidies could help alleviate potential regressivity by enabling consumers to switch to more healthy products without incurring additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the poor are more responsive to price increases, they benefit more from higher taxes as commitment mechanisms. Remler (2004) addressed qualitatively the different underlying notions of regressivity. In this paper, we investigate thoroughly whether Warner's contention that cigarette tax increases are a movement toward progressivity in a traditional framework is true empirically.…”
Section: Introductionmentioning
confidence: 99%
“…15 We must also be conscious that the imperative to reduce specific pathologies, however logical, reflects personal and structural biases-research methods, funding systems, and career trajectories that are tied to and show impact on individual diseases.…”
Section: Public Health Law Researchmentioning
confidence: 99%